ARTHROSCOPIC ASSISTED PERCUTANEOUS SCREW FIXATION OF PYLON FRACTURE: CASE REPORT - Mitev, Konstantin (Journal of Morphological Sciences; Vol 2 No 1 (2019): JMS, 2019)
We report a case of 24 year old female, with closed pylon tibial  fracture  ,treated with arthroscopic assisted percutaneous osteosynthesis. Surgical technique â€“ Ankle arthroscopy with debridement, sequestrectomy fracture reposition  and under fluoroscopic  imaging , percutaneous screw     fixation  was done. For objective evaluation of the range of motion, and subjective satisfaction from the operation and  pain score  we used American ankle and foot score. Follow up was done at 3 and 6 months  postoperatively and 1 month after screws removal. Excelent postoperative result, with no surgical complication was present.